2014
DOI: 10.1063/1.4879677
|View full text |Cite
|
Sign up to set email alerts
|

Metallic filament formation by aligned oxygen vacancies in ZnO-based resistive switches

Abstract: Articles you may be interested inMethod of choice for fabrication of high-quality ZnO-based Schottky diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In case of LRS, a nearly ohmic electronic conduction behaviour characterized with I α V was observed, suggesting that electrons flow in a metallic-like conductive path in agreement with a filamentary type of resistive switching. This ohmic-like behaviour can be ascribed to a depression of the local Schottky barrier at the Pt/ZnO interface in correspondence of the conductive path, as theoretically discussed by Gu [55]. A different electronic conduction mechanism can be identified instead in the HRS.…”
Section: Nw Length (µM)mentioning
confidence: 69%
See 1 more Smart Citation
“…In case of LRS, a nearly ohmic electronic conduction behaviour characterized with I α V was observed, suggesting that electrons flow in a metallic-like conductive path in agreement with a filamentary type of resistive switching. This ohmic-like behaviour can be ascribed to a depression of the local Schottky barrier at the Pt/ZnO interface in correspondence of the conductive path, as theoretically discussed by Gu [55]. A different electronic conduction mechanism can be identified instead in the HRS.…”
Section: Nw Length (µM)mentioning
confidence: 69%
“…Indeed, a switching mechanism based on the electrochemical metallization memory (ECM) effect, that involves the migration of host ions extracted from the metal electrodes, can be safely excluded due to the choice of electrochemically inert Pt electrodes [53,54]. According to first-principle calculations by Gu [55], that analyzed the metallic filament formation driven by oxygen ion movement under applied electric field in Pt/ZnO/Pt devices, the conductive channel in the ON state is related to valence electrons corresponding to the extended defects of alignment of oxygen vacancies that show delocalized properties. Note also that a VCM mechanism of switching was previously reported in a wide range of resistive switching devices based on ZnO thin films and contacted by means of Pt electrodes [56,57].…”
Section: Resistive Switching Mechanismmentioning
confidence: 99%
“…Further, it influences the oxygen vacancy (V O ) formations during the electroforming of conductive filaments [ 7 ]. Jing et al and Gu et al, have explained the mechanism [ 8 , 9 ]. They have shown that the oxygen vacancy defect states and are originated by the O-deficient Zn orbitals, and the electron and hole injection under the electric field in the ZnO layer controls the formation and rupture of the oxygen-vacancy-related conductive filaments.…”
Section: Introductionmentioning
confidence: 99%